Analisis Pengaruh Return on Assets dan Debt to Equity Ratio Terhadap Pertumbuhan Laba pada PT Indika Energy Tbk - Sri Wahyuningsih; M. Rimawan; Rahmatia (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) on profit growth at PT Indika Energy Tbk during the 2015–2024 period. The study employed an associative quantitative approach using secondary data obtained from the company's annual financial statements. The sample consisted of ten years of financial reports selected through purposive sampling. Data analysis was conducted using multiple linear regression, preceded by classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results indicate that Return on Assets (ROA) does not have a significant partial effect on profit growth, as evidenced by a significance value of 0.325 (>0.05). Likewise, Debt to Equity Ratio (DER) does not significantly affect profit growth, with a significance value of 0.173 (>0.05). Simultaneously, ROA and DER also do not have a significant effect on profit growth, as indicated by an F significance value of 0.311 (>0.05). The coefficient of determination (R²) of 0.283 shows that 28.3% of the variation in profit growth can be explained by ROA and DER, while the remaining 71.7% is influenced by other factors outside the model. These findings suggest that profit growth at PT Indika Energy Tbk is affected by factors beyond profitability and leverage ratios.